Maternal milk fat globule membrane enriched gut L. murinus and circulating SCFAs to improve placental efficiency and fetal development in intrauterine growth restricted mice model - Cuiping Feng; Yujun Wu; Xiangyu Zhang; Shuxian Wang; Junjun Wang; Huixia Yang (Gut Microbes)
Intrauterine growth restriction (IUGR) caused by placental dysfunctions leads to fetal growth defects. Maternal microbiome and its metabolites have been reported to promote placental development. Milk fat globule membrane (MFGM) is known for its diverse bioactive functions, while the effects of gestational MFGM supplementation on the maternal gut microbiota, placental efficiency, and fetal development remained unclear. In this study, low protein diet-induced IUGR decreased the litter birth weight, fetal birth weight, and the fetal/placental ratio in pregnant mice, while gestational MFGM supplementation restored these impairments. Meanwhile, MFGM supplementation during gestation enriched intestinal Lactobacillus murinus (L. murinus) and increased luminal and circulating short chain fatty acids (SCFAs) in IUGR pregnant mice, which improved placental efficiency and fetal development due to an enhanced antioxidant capacity and a decreased inflammation. In addition, fecal microbiota transplantation (FMT) with MFGM-derived microbiota reprinted the promoted phenotypes of maternal litter characteristics, gut L. murinus enrichment, placental efficiency, and fetal gut development in MFGM-fed pregnant mice, which were also recapitulated by exogenous administration with L. murinus or SCFAs cocktail. Mechanically, MFGM, MFGM-derived microbiota, L. murinus, or SCFAs cocktail activated IUGR-induced depressive phosphorylation of PI3K-Akt signaling in the placenta. Moreover, in vitro placental cells cultivation under amino acid shortage model (AAS) or oxygen-glucose shortage model (OGS) was used to validate that MFGM-derived key microbial and circulating SCFAs cocktails can alleviate placental oxidative stress and inflammation via activating PI3K/Akt signaling. Taken together, gestational MFGM supplementation enriched intestinal L. murinus and circulating SCFAs of IUGR pregnant mice, thereby improving placental efficiency, fetal growth, and intestinal functions of IUGR fetus. Our findings will provide theoretical support for the application of MFGM in the maternal–placental-fetal nutrition to address pregnancy malnutrition-induced IUGR.